Trends in agriculture, non-farm sector and rural employment in India: An insight from state level analysis - VENKATESH, P; L, NITHYASHREE M; SANGEETHA, V; PAL, SURESH (The Indian Journal of Agricultural Sciences, 2015)
The experience from developed countries established that decline in the share of agriculture in national GDP is an indication of economic progress of the country. However, commensurate with the decline in GDP contribution, the dependency of population on agriculture is also expected to decline. In this context, this paper analysed the performance of Indian agriculture in terms of growth, employment and output using secondary data in the last two decades (1990- 2010) at the national level and also with the special focus on the major states. Specifically the paper discuses: (i) agriculture’s contribution in the national employment and income, (ii) sectoral changes in employment across the states, and (iii) determinants of rural non-farm employment (RNFE). The results have shown that percentage share of agriculture in employment has declined during last two decades, but it was not comparable to the extent of decline in its share in the national GDP. Dependency on agriculture declined for the male workers, while it increased for female workers in the recent decade, indicating feminization of agriculture. The RNFE in different states exceeded over 25 per cent for 12 out of 17 states, and it was significantly high in the states of Kerala, Jammu and Kashmir and Punjab. The determinant analysis revealed that the infrastructure development, agricultural growth and farm-size are the major factors which positively influenced the RNFE, whereas the share of SC and ST population in rural population had negative effect on the growth of RNFE.